Genetic Testing for Parkinson Disease: Are We Ready?. Issue 1 (February 2021) - Cook, Lola; Schulze, Jeanine; Kopil, Catherine; Hastings, Tara; Naito, Anna; Wojcieszek, Joanne; Payne, Katelyn; Alcalay, Roy N.; Klein, Christine; Saunders-Pullman, Rachel; Simuni, Tatyana; Foroud, Tatiana
Abstract : Purpose of Review: With the advent of precision medicine and demand for genomic testing information, we may question whether it is time to offer genetic testing to our patients with Parkinson disease (PD). This review updates the current genetic landscape of PD, describes what genetic testing may offer, provides strategies for evaluating whom to test, and provides resources for the busy clinician. Recent Findings: Patients with PD and their relatives, in various settings, have expressed an interest in learning their PD genetic status; however, physicians may be hesitant to widely offer testing due to the perceived low clinical utility of PD genetic test results. The rise of clinical trials available for patients with gene-specific PD and emerging information on genotype-phenotype correlations are starting to shift this discussion about testing. Summary: By learning more about the various genetic testing options for PD and utility of results for patients and their care, clinicians may become more comfortable with widespread PD genetic testing in the research and clinical setting.